Empirical Analysis on the Relationship between Capital Market and Economic Growth in Nigeria - Olusola, AJAYI Olakunle; Adedigba, ABINA Praise; Casper, IJOMAH Nwabaku (Journal of Asian Business Strategy, 2019)
Capital can be categorized into human and material capital, the latter in its liquid form helps in the allocation and mobilization of savings. This study investigates the relationship between capital market and performance of Nigeria economy, gross domestic product was used to proxy performance of Nigeria economy while capital market was proxied by market capitalization, all share index and total value of transaction. Time series data between the period of 1985 to 2017 was sourced from Central Bank of Nigeria, and statistical bulletin 2018. The study made use of descriptive statistics, Phillip Peron, unit root test, Johansen Co-integration, granger causality test and vector error correction estimate. Based on the findings of the vector error correction estimate, the study, therefore, recommends that there is a need for the free flow of information, this can be achieved by increasing the publicity of market information, as this will increase the volume of transactions in the market.